Ilizarov Fixator Combined With an Intramedullary Nail for Tibial Nonunions With Bone Loss: Is It Effective? - Gulabi, Deniz (Clin Orthop Relat Res, 2014)
BACKGROUND: Treatment of tibial nonunion with bone loss is extremely difficult. A variety of techniques have been described, but each has shortcomings, in particular prolonged external fixation time as well as serious complications such as nonunion and infection. Accordingly, we developed a technique that seeks to reduce these complications by using a circular external fixator in addition to an intramedullary nail to achieve union, limb lengthening, and stability of the regenerated segment. DESCRIPTION OF TECHNIQUE: First, the pseudoarthrosis area is resected, and acute compression is continued until bone contact at the docking site was achieved. Then primary grafting is applied to the docking site using a graft harvested from the patient’s iliac bone, and the predrilled nail holes localized on the middle segment of the tibia are locked with a free-hand technique. Finally, lengthening is performed to overcome the leg-length discrepancy with an external fixator. METHODS: Between 2008 and 2011, this technique was used to treat five patients with tibial nonunion with bone loss. All patients were available for a minimum of a 14-month followup (mean, 30 months; range, 14–58 months). General indications for the procedure were age older than 16 years, tibial nonunion with bone loss, and the absence of any psychiatric disorder. We evaluated external fixation time, external fixation index (defined as the duration of external fixation in months divided by the total amount of bone transported and/or the amount of lengthening in centimeters), and time to union on plain radiographs, clinical results using the Paley bone and functional assessment scores, and postoperative complications from chart review. RESULTS: The external fixation time was 4 months (range, 3–5 months), and the average external fixation index was 0.4 months/cm. The mean time to bone union was 4.6 months (range, 3.5–5.5 months). All angles were determined to be in the normal range. No patients developed refracture or malalignment either on the docking site or the osteotomy site. Paley bone evaluation results were excellent in all five patients, and Paley functional results were excellent in four and good in one. We observed 10 pin-site infections as minor complications, and one patient was left with a residual equinus deformity of 5° as a major complication according to the Paley classification. CONCLUSIONS: Our technique combining acute shortening and distraction osteogenesis had promising results for the treatment of tibial nonunion with bone loss in a small group of patients. However, future studies directly comparing available approaches to this difficult problem are required. Because this problem is uncommon, these studies will almost certainly require the cooperation of multiple large participating centers. LEVEL OF EVIDENCE: Level IV, therapeutic study. See Guidelines for Authors for a complete description of levels of evidence.